Five-Year Long-Term Prognosis of Epileptic Children After Hemispheric Surgery: A Systematic Review and Meta-analysis. Issue 23 (June 2016) - Cao, Kai; Liu, Meiling; Wang, Chao; Liu, Qingrong; Yang, Kun; Tao, Lixin; Guo, Xiuhua
Abstract : Abstract: To estimate children's long-term seizure outcomes after hemispheric surgery and the associated predictors. A systematic review of 4 databases and a meta-analysis were performed from January 1, 1995 to August 31, 2015. The databases included PubMed, Embase, Science Direct, and Web of Science; patients were classified into the Engel Class I group and the Engel Class II to IV group, according to their seizure outcomes. Nine potential predictors were then stratified across the groups and estimated using the Wilcoxon rank-sum test for continuous variables and the Chi-squared test for categorical variables. The search yielded 15 retrospective studies, with a total sample size of 380. Five years after surgery, 268 (0.71, 95% confidence interval [CI]: 0.64–0.78) children were seizure free; the seizure onset age in the Engel Class I group was significantly higher than that of the Engel Class II to IV group (standardized mean difference [SMD] = 0.26, 95% CI: 0.03–0.49, P = 0.028); specifically, when predicting the positive long-term outcomes, the odds ratio for late onset age (≥3.6 months, median value of the Engel Class II–IV group) versus early onset age was 2.65 (95% CI: 1.454–4.836, z = 3.18, P = 0.001). The abnormal magnetic resonance imaging (MRI) findings were more predictive for positive seizure outcomes than the normal findings (odds ratio [OR] = 4.60, 95% CI: 1.27–16.62, P = 0.02). Following hemispheric surgery, the long-term prognosis of children with epilepsy was good. Late seizure onset (age ≥ 3.6 months) and abnormal MRI findings were positive predictors for long-term seizure control in children.